Ten-year cardiovascular risk estimation in type 2 diabetes in Europe using the novel SCORE2-Diabetes model - G. G. Arabidze; M. N. Mamedov; H. R. Akhundova (Кардиоваскулярная терапия и профилактика, 2024)
The article presents a validated prognostic score (SCORE2-Diabetes) developed by a group of European researchers in collaboration with the European Society of Cardiology (ESC) for 10-year cardiovascular risk in type 2 diabetes (T2D) in Europe. The SCORE2-Diabetes risk calculator was developed based on the SCORE2 algorithms using data from patients with T2D and no prior cardiovascular disease (CVD). The authors developed a novel risk model that takes into account sex, age, age at diagnosis of T2D, glycated hemoglobin level, estimated glomerular filtration rate, smoking, systolic blood pressure, total cholesterol and high-density lipoprotein cholesterol levels, based on cardiovascular morbidity rate in 4 regions of Europe. The model included 38602 cases of CVD and showed good discrimination and calculation improvement compared to SCORE2 (change in C-index from 0,009 to 0,031) depending on the T2D-related factors. The authors consider adaptation of the SCORE2-Diabetes risk model to modern populations, including in the Russian Federation. Comparative analysis with similar models, assessing the advantages and disadvantages of various CVD risk models in patients with T2D is presented.Conclusion. SCORE2-Diabetes improves the identification of individuals at higher cardiovascular risk in Europe based on new validated data from the European region.